IMPLEMENTASI ALGORITMA FISHER YATES UNTUK PENGACAKAN SOAL PADA APLIKASI MOBILE LEARNING KUIS FIQIH BERBASIS ANDROID - Rio Priantama; Yuda Priandani (FKOM UNIKU, 2019)
The conventional learning process carried out face-to-face, is less effective as a source of learning, because the focus of students' interest has now shifted to their device so that students have difficulty repeating learning material. This study aims to produce learning media based on mobile learning on the android platform which is used as a source of learning fiqh applications for students. This mobile learning application is built by applying the Fisher Yates Shuffling algorithm or commonly known as the Fisher Yates algorithm which is now widely used in the process of developing randomization applications. This randomization method is the optimal randomization method in application development, being able to randomize the amount of material about the science of jurisprudence and prevent cheating users who only memorize answers without understanding the material when the questions are fixed or not random. Applications are built using MySQL as a database designed to manage and manipulate data quickly and easily. PHP and Perl are used as scripting programming languages for the internet and collaborate on the Android platform. The system development method used is RUP (Rational Unified Process) by collecting various best practices found in the software development industry.System testing is done using a white box and black box testing shows that the Fisher Yates algorithm can be applied in the mobile learning quiz application as a randomizer about questions. User Acceptance Model (UAT) test results show that this mobile learning application can help the process of learning the science of jurisprudence as well as being a reference in seeing the ability of students to learn the science of jurisprudence. Keywords: Mobile learning, Fisher Yates Algorithm, Fiqih, MySQL, RUP, UML